Relation between Trade Openness, Capital Openness and Government Size in India: An Application of Bounds Testing-ARDL Approach to Co-integration. (February 2014) - Dixit, Vikas
It is generally argued that when an economy opens up, it is exposed to external risk and therefore, more government expenditure is demanded to compensate that risk and the increasing level of economic inequalities associated with openness. On the other hand, there is an opposite view which says that with higher capital openness, it would become difficult for national governments to tax and to issue public debt to finance public expenditures, as capital may easily move abroad. An attempt is, therefore, made in this article to understand the nature of relationship between trade openness, capital openness and government size in India over the period from 1980–1981 to 2009–2010. The empirical results of this study seems to challenge in general the validity of the compensation hypothesis, but finds support for Wagner's law for most of the measures of government size. We also find evidences to favour efficiency hypothesis for some measures of government size, according to which, there exists a negative relationship between capital openness and government size. We have also been able to establish causal links between trade openness, capital openness and government size using TYDL non-causality test, which, indeed, not only complements the findings of autoregressive distributed lag (ARDL) estimation, but also indicates the causal nexus in those cases where no long-run or short-run relationship is observed.